Wybrane koncepcje przezwyciężania kryzysu ekologicznego - Abdank-Kozubski, Andrzej (Śląskie Studia Historyczno-Teologiczne, 2011)
Burdening a human with responsibility for the observed ecological crisis cannot cover the entire domain of questions concerning his role in nature. This is because a human is naturally able to correct his faults and negligence. As a unique creature, a human is able to enrich his relation with natural environment with a sense of being responsible for this environment. The latter is, however, possible provided human is able to recognize and appreciate his own rational and moral capability. Thanks to that, a human may also recognize his own limitations and consequently, try to compensate them rationally and morally. Three proposals for an outlook on a human as a warranty for conquering ecological crisis are presented in the article: these are the concepts of Hans Jonas, Ludwik Schäfer and Konrad Lorenz.